Perlindungan Hukum Bagi Konsumen dalam Pemenuhan Kebutuhan Air Bersih (Qawanin Jurnal Ilmu Hukum, 2021)
This study discusses about Undang-Undang Number 8 of 1999 concerning Consumer Protection. Legal protection for consumers includes the fulfillment of consumer rights by providers of goods and/or services. One of the regionally owned enterprises owned by the Wajo Regency Government, namely the Regional Drinking Water Company, has the authority to manage water resources. Consumers of the Regional Drinking Water Company located in the Grandhill housing complex, Atakkae Village, Tempe District, Wajo Regency, complain that the process of distributing clean water is not optimal so that people often lack water. The Regional Drinking Water Company has made every effort to distribute clean water to all consumers. The distribution mechanism is carried out in turns with an interval of one day so that the distribution of clean water can be evenly distributed. The inadequate distribution of clean water is caused by several factors namely lack of water pumps, repair of water treatment plants and the increasing number of people in Wajo Regency who need clean water. Although the Regional Drinking Water Company has not provided clean water services optimally due to inhibiting factors, from the point of view of their responsibilities based on Undang-Undang Number 8 of 1999 Article 7 letter c "treats and serves consumers properly and honestly and is not discriminatory." Drinking Wajo Regency has served consumers properly and honestly and is not discriminatory.Abstrak:Penelitian ini membahas Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen. Perlindungan hukum bagi konsumen mencakup pemenuhan hak-hak konsumen oleh penyedia barang dan/ atau jasa. Salah satu Badan Usaha Milik Daerah yang dimiliki Pemerintah Kabupaten Wajo yaitu Perusahaan Daerah Air Minum memiliki kewenangan mengelola sumber daya air. Konsumen Perusahaan Daerah Air Minum yang berada di kompleks perumahan Grandhill Kelurahan Atakkae Kecamatan Tempe Kabupaten Wajo mengeluhkan proses pendistribusian air bersih yang tidak maksimal sehingga masyarakat sering kekurangan air. Perusahaan Daerah Air Minum telah berusaha semaksimal mungkin untuk mendistribusikan air bersih kepada seluruh konsumen. Mekanisme pendistribusian dilakukan secara bergilir dengan selang satu hari agar pembagian air bersih dapat merata. Kurang maksimalnya pendistribusian air bersih disebabkan oleh beberapa faktor yaitu kurangnya pompa air, perbaikan Instalasi Pengolahan Air dan terus bertambahnya jumlah penduduk di Kabupaten Wajo yang membutuhkan air bersih. Walaupun Perusahaan Daerah Air Minum belum memberikan layanan air bersih secara maksimal karena adanya faktor penghambat akan tetapi dari sisi tanggung jawabnya berdasarkan Undang-Undang Nomor 8 Tahun 1999 Pasal 7 huruf c “memperlakukan dan melayani konsumen secara benar dan jujur serta tidak diskriminatif” Perusahaan Daerah Air Minum Kabupaten Wajo telah melayani konsumen secara benar dan jujur seta tidak diskriminatif.